Prevention and Control of Communicable and Non-Communicable Diseases - Sipra Barutu (Journal Health of Indonesian, 2025)
Communicable and non-communicable diseases are two major challenges in global and national health systems, including in Indonesia. Communicable diseases such as tuberculosis, malaria, and HIV/AIDS are still the main causes of morbidity and mortality, while non-communicable diseases such as heart disease, cancer, and diabetes mellitus have increased significantly along with changes in lifestyle and epidemiological transition. This article is a literature review that aims to describe prevention and control strategies for both groups of diseases based on scientific sources and official reports. The results of the study indicate that surveillance-based approaches, public education, health promotion, and multidisciplinary interventions are key to overcoming these health problems. Therefore, strengthening preventive and promotive policies must be a priority in the Indonesian health system to reduce the burden of disease in the future.